Promoting Student Questioning in EFL Classroom: Teacher’s Strategies in 2013 Curriculum Context - Ma'rufah, Desi Wijayanti (OKARA: Jurnal Bahasa dan Sastra, 2021)
The government expects that the learning process in the 2013 curriculum uses inspiring, interactive, fun, and challenging activities that engage students’ participation in the class. The students’ involvement and critical thinking in meaningful learning are increased when the students ask questions productively in the classroom. However, Indonesian EFL students are indicated to have little space for interacting in the classroom, not to mention questioning. For that reason, this study aims to explore the teacher’s strategies in encouraging student questioning in EFL class. A qualitative research design was conducted through observation, interview, and questionnaire. The findings showed that the teacher used various strategies in promoting student questioning: providing a free question time, using turn-taking questioning, evolving a receptive classroom atmosphere, and giving explicit instruction in the teaching and learning process. Finally, this study implies that Indonesian EFL students would be encouraged to ask questions actively when: (a) the activities to pose questions were set; (b) objects or topics of questioning to scaffold students were provided; (c) classroom climate was accepted questions; (d) clear instructions were given. Thus, student questioning could be raised through instructional interventions from the teacher.